2015
DOI: 10.3329/ralf.v2i1.23033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial load in marketed broiler meat at Mymensingh district of Bangladesh and its public health implications

Abstract: An investigation was conducted to assess the bacteriological quality of 30 samples of fresh broiler thigh meat samples sold in different retail markets in Mymensingh. Total viable count (TVC), total coliform count (TCC), total salmonella count (TSC) and total campylobacter count (TCpC) in meat samples of different broiler markets like K.R. at BAU campus, Boyra and Kewatkhali were determined. Mean of TVC, TCC, TSC and TCpC for the K.R. at BAU campus, Boyra and Kewatkhali markets were 5.69, 6.03, 6.17 log10 CFU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…In most cases of processed broiler meat, the high quantity of coliform bacteria causes severe food poisoning especially among children. In this study, the lowest value of TCC was found 1.6 × 10 3 CFU/gm (Sample 3) and the highest was 1.5 × 10 5 [49] and many other studies also showed the similar result regarding TCC. The isolation of coliform bacteria also indicates probable fecal contamination and the prevalence of fecal coliform was recorded as about 33% in this study where, fecal contamination were detected in five samples (2, 7, 8, 11 and 13).…”
Section: Total Coliform Count (Tcc)supporting
confidence: 78%
“…In most cases of processed broiler meat, the high quantity of coliform bacteria causes severe food poisoning especially among children. In this study, the lowest value of TCC was found 1.6 × 10 3 CFU/gm (Sample 3) and the highest was 1.5 × 10 5 [49] and many other studies also showed the similar result regarding TCC. The isolation of coliform bacteria also indicates probable fecal contamination and the prevalence of fecal coliform was recorded as about 33% in this study where, fecal contamination were detected in five samples (2, 7, 8, 11 and 13).…”
Section: Total Coliform Count (Tcc)supporting
confidence: 78%